2014
DOI: 10.1111/ijac.12295
|View full text |Cite
|
Sign up to set email alerts
|

SiC Foams Decorated with SnO2 Nanostructures for Room Temperature Gas Sensing

Abstract: Cell walls of the commercial silicon carbide (SiC)‐based foams were decorated by one‐dimensional tin dioxide (SnO2) nanostructures. Thermal evaporation of SnO2 powder with the assistance of a Au catalyst in inert atmosphere caused the formation of SnO2 nanobelts on the pore surfaces. The room temperature (RT) ammonia (NH3) and nitrogen dioxide (NO2) gas sensing behaviors were investigated systematically in both dry and humid air atmosphere with/without UV activation. The results were compared to those for bare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 37 publications
(54 reference statements)
1
13
0
Order By: Relevance
“…In 2014 two reports were published on the growth of SnO 2 nanowires using evaporation condensation with SnO 2 powder as source material but a different catalyst was used to grow the nanowires. In the first report, the authors showed the results of SnO 2 nanowires grown on SiC substrate using Au as a catalyst [43]. Deposition parameters (E t = 1370 °C, P = 100 mbar, S t = 500 °C) were similar to those first reported by Comini et al [36].…”
Section: Surface Morphology Investigation Of Nanowiressupporting
confidence: 64%
“…In 2014 two reports were published on the growth of SnO 2 nanowires using evaporation condensation with SnO 2 powder as source material but a different catalyst was used to grow the nanowires. In the first report, the authors showed the results of SnO 2 nanowires grown on SiC substrate using Au as a catalyst [43]. Deposition parameters (E t = 1370 °C, P = 100 mbar, S t = 500 °C) were similar to those first reported by Comini et al [36].…”
Section: Surface Morphology Investigation Of Nanowiressupporting
confidence: 64%
“…As previously reported by our group (Figure 11a), the desorption process under UV light is faster than in dark, leading to a complete recovery of the baseline. In most cases, there is no memory effect at temperatures higher than 250 °C [94]. At RT, the enhancement of the response by UV-irradiation is clearly visible, as reported in Figure 11b.…”
Section: Surface Photoactivationmentioning
confidence: 68%
“…For example, in the case of UV-irradiated SnO 2 RGTO, the best results for the detection of CO were obtained at 15 mW/m 2 . At higher values of applied power, the response is lower or comparable to the dark response, due to the prevalence of the photodesorption effect [94].…”
Section: Surface Photoactivationmentioning
confidence: 98%
See 2 more Smart Citations